Effect of a combination GOS/FOS® prebiotic mixture and interaction with calcium intake on mineral absorption and bone parameters in growing rats - Bryk, Gabriel (2014)
AIM: Increasing calcium intake is the most effective strategy for avoiding Ca deficit. However, if intake remains inadequate, improving Ca absorption becomes an important tool to optimize Ca homeostasis and bone health. PURPOSE: The effect of a mixture of GOS/FOS(®) 9:1 added to a normal- or low-Ca diets on Ca absorption and bone mineralization, density and structure was investigated, in a model of growing rats. Several colonic parameters to help support the findings were also evaluated. RESULTS: Weanling Wistar rats received one of the four experimental AIN-93G diets: C5: 0.5% Ca; C3: 0.3% Ca; P5: 0.5% Ca + 5.3% GOS/FOS(®); P3: 0.3% Ca + 5.3% GOS/FOS(®) until 50 days (T = 50). At T = 50, lactobacillus and cecum weights were higher, whereas cecum pH was lower in P5 and P3 versus C5 and C3 (p < 0.001). At T = 50, fecal Ca, Mg and P were lower and their absorptions (mg/dL) were higher in P5 and P3 versus C5 and C3, respectively (p < 0.05). Ca, Mg and P absorption % was higher in P5 and P3 versus C5 and C3 (p < 0.001). Femur Ca and P content, bone mineral content, trabecular bone mineral density, tibia length, bone volume, osteoblast surface, stiffness and elastic modulus were higher in P5 and P3 versus C5 and C3 (p < 0.05). Despite the lower Ca content, P3 group reached similar values than C5 in all these latter parameters. CONCLUSIONS: Supplementing diets with the GOS/FOS(®) mixture increased bone mineralization, density and structure due to an increase in Ca, P and Mg absorptions. Thus, this prebiotic mixture may help to improve bone development in a period of high calcium requirements.